A Pediatric Approach to Ventilator-Associated Events Surveillance. (5th December 2016) - Cocoros, Noelle M.; Priebe, Gregory P.; Logan, Latania K.; Coffin, Susan; Larsen, Gitte; Toltzis, Philip; Sandora, Thomas J.; Harper, Marvin; Sammons, Julia S.; Gray, James E.; Goldmann, Donald; Horan, Kelly; et al.
Abstract : OBJECTIVE: Adult ventilator-associated event (VAE) definitions include ventilator-associated conditions (VAC) and subcategories for infection-related ventilator-associated complications (IVAC) and possible ventilator-associated pneumonia (PVAP). We explored these definitions for children. DESIGN: Retrospective cohort SETTING: Pediatric, cardiac, or neonatal intensive care units (ICUs) in 6 US hospitals PATIENTS: Patients ≤18 years old ventilated for ≥1 day METHODS: We identified patients with pediatric VAC based on previously proposed criteria. We applied adult temperature, white blood cell count, antibiotic, and culture criteria for IVAC and PVAP to these patients. We matched pediatric VAC patients with controls and evaluated associations with adverse outcomes using Cox proportional hazards models. RESULTS: In total, 233 pediatric VACs (12, 167 ventilation episodes) were identified. In the cardiac ICU (CICU), 62.5% of VACs met adult IVAC criteria; in the pediatric ICU (PICU), 54.2% of VACs met adult IVAC criteria; and in the neonatal ICU (NICU), 20.2% of VACs met adult IVAC criteria. Most patients had abnormal white blood cell counts and temperatures; we therefore recommend simplifying surveillance by focusing on "pediatric VAC with antimicrobial use" (pediatric AVAC). Pediatric AVAC with a positive respiratory diagnostic test ("pediatric PVAP") occurred in 8.9% of VACs in the CICU, 13.3% of VACs in the PICU, and 4.3% of VACs in the NICU. Hospital mortality was increased, and hospital and ICU length of stay and duration of ventilation were prolonged among all pediatric VAE subsets compared with controls. CONCLUSIONS: We propose pediatric AVAC for surveillance related to antimicrobial use, with pediatric PVAP as a subset of AVAC. Studies on generalizability and responsiveness of these metrics to quality improvement initiatives are needed, as are studies to determine whether lower pediatric VAE rates are associated with improvements in other outcomes. Infect Control Hosp Epidemiol 2017;38:327–333